Translating Technology Into Speech–Language Pathology Practice: Qualitative Interviews Using Transcranial Magnetic Stimulation as a Case Study - Williams, Ellen E. R.; Hordacre, Brenton; Rogasch, Nigel C.; Goldsworthy, Mitchell; Attrill, Stacie (International journal of language & communication disorders, 2025)
ABSTRACT Background Technologies such as videofluoroscopy, therapy applications, and telehealth have been translated into the clinical toolkit of many speech–language pathologists (SLPs). Transcranial magnetic stimulation (TMS) is an emerging technology that shows therapeutic promise for communication and swallowing disorders and, once suitable for clinical use, SLPs will likely be responsible for delivering this treatment. As such, it is critical that SLP opinions and attitudes towards TMS, as well as broader translation issues facing the profession, are considered early in the TMS research and translation process. Aims (1) To explore in‐depth the determinants of SLP behaviour that could influence translation of TMS into speech–language pathology practice; and (2) to examine these behavioural determinants within the context of profession‐wide research‐to‐practice gaps. Methods and Procedures Semi‐structured interviews were conducted with 10 SLPs, who were classified into novice, intermediate, or expert TMS knowledge/experience levels. Reflexive thematic analysis conventions were used to inductively and deductively code interview data. The refined Theoretical Domains Framework (rTDF) informed study design, analysis, interpretation, and reporting, and served as a theoretical lens through which recommendations were developed. Outcomes and Results Four main themes were derived from interview data, representing four overarching determinants of SLP behaviour: actual knowledge/experience; perceptions of professional role and capabilities; optimism/pessimism mindset and emotions; and environmental factors. Results within each theme were categorised as TMS‐specific (aim 1) or profession‐wide (aim 2). Conclusions and Implications Many TMS‐specific behavioural determinants could impact the translation of TMS into speech–language pathology, however these exist against the backdrop of larger, profession‐wide translation issues. A taxonomy of nine recommendations for bridging technology translation gaps in speech–language pathology is provided, with a view to facilitating future implementation of TMS and other technologies. WHAT THIS PAPER ADDS What is already known on the subject Transcranial magnetic stimulation (TMS) might one day be used as a treatment for communication and swallowing disorders, and speech–language pathologists (SLPs) will likely be responsible for delivering this treatment. Previous research has investigated SLPs’ opinions and attitudes towards TMS to identify determinants of SLP behaviour that could impact translation of TMS into practice. However, more in‐depth investigation is required within the context of profession‐wide translation issues. What this paper adds to the existing knowledge The present study highlights behavioural determinants that could impact translation of TMS, as well as profession‐wide research‐to‐practice gaps. We suggest important strategies and lines of enquiry to bridge translation gaps for use of technologies in speech–language pathology, which are summarised as a taxonomy of nine recommendations. What are the potential or actual clinical implications of this work? Results from this study may help SLPs to acknowledge and characterise translation issues in their own practice and across the broader profession. Our taxonomy of recommendations can be used in clinical, research, and implementation science settings to address technology translation issues in speech–language pathology, facilitating future integration of TMS and other technologies into practice.